Long Term Survivors with Metastatic Pancreatic Cancer Treated with Gemcitabine Alone or Plus Cisplatin: a Retrospective Analysis of an Anatolian Society of Medical Oncology Multicenter Study - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2012)
Background: The majority of patients with pancreatic cancer present with advanced disease. Systemic chemotherapy has limited impact on overall survival (OS) so that eligible patients should be selected carefully. The aim of this study was to analyze prognostic factors for survival in Turkish advanced pancreatic cancer patients who survived more than one year from the diagnosis of recurrent and/or metastatic disease and receiving gemcitabine (Gem) alone or gemcitabine plus cisplatin (GemCis). Methods: This retrospective evaluation was performed for patients who survived more than one year from the diagnosis of recurrent and/or metastatic disease and who received gemcitabine between December 2005 and August 2011. Twenty-seven potential prognostic variables were chosen for univariate and multivariate analyses to identify prognostic factors associated with survival. Results: Among the 27 variables in univariate analysis, three were identified to have prognostic significance: sex (p = 0.04), peritoneal dissemination (p = 0.02) and serum creatinine level (p = 0.05). Multivariate analysis by Cox proportional hazard model showed only peritoneal dissemination to be an independent prognostic factor for survival. Conclusion: In conclusion, peritoneal metastasis was identified as an important prognostic factor in metastatic pancreatic cancer patients who survived more than one year from the diagnosis of recurrent and/or metastatic disease and receiving Gem or GemCis. The findings should facilitate pretreatment prediction of survival and can be used for selecting patients for treatment.
Keywords: Pancreas; cancer; gemcitabin; prognosis; long term survivors; RANDOMIZED PHASE-III; PROGNOSTIC-FACTORS; ADENOCARCINOMA; CHEMOTHERAPY; TRIAL